Value of integrated PET-IVIM MRI in predicting Ki-67 expression in newly diagnosed prostate cancer - Xiao, Liu; Li, Yuhao; Xing, Yikai; Li, Lin (Scientific reports, 2025)
Accurate assessment of Ki-67 expression in patients with prostate cancer (PC) is paramount. Therefore, this study aimed to assess the value of integrated Gallium-68( 68 Ga)-prostate-Specific membrane antigen-11 (PSMA) Positron Emission Tomography/Intravoxel Incoherent Motion Magnetic Resonance Imaging (PET/IVIM MRI) in predicting Ki-67 expression in newly diagnosed PC. A retrospective analysis was conducted on 37 newly diagnosed PC patients who underwent 68 Ga-PSMA-11 PET/MR for staging. Maximum Standardized Uptake Value( SUVmax) and IVIM parameters of lesions were quantified. Patients were stratified into low-risk (Ki-67 < 5%) and high-risk groups (Ki-67 > 5%). SUVmax and IVIM parameters were compared between the two groups. Of the 37 patients, 29 were categorized as high risk, while 8 were classified as low risk. The high-risk group exhibited significantly higher SUV max (21.4 ± 11.3 vs. 11.2 ± 8.5, P = 0.025) and lower Standard apparent diffusion coefficient (ADC) (0.0011 ± 0.00023 vs. 0.0014 ± 0.00039, P = 0.005) compared to the low-risk group. Receiver operating characteristic (ROC) analysis determined optimal cut-off values for predicting high-risk patients as 7.64 for SUV max (sensitivity: 96.6%, specificity: 59.1%) and 0.0013 for standard ADC (sensitivity: 89.7%, specificity: 52.3%). Integrated assessment of SUVmax and standard ADC using 68 Ga-PSMA-11 PET-IVIM MRI may aid in predicting Ki-67 expression, with optimal thresholds of 7.67 for SUVmax and 0.0013 for standard ADC. These findings offer novel insights into evaluating the biological behavior of prostate cancer tumors in patients undergoing PET/MR imaging.